Anxiety Cells in a Hippocampal-Hypothalamic Circuit - Jimenez, Jessica C; Su, Katy; Goldberg, Alexander R; Luna, Victor M; Biane, Jeremy S; Ordek, Gokhan; Zhou, Pengcheng; Ong, Samantha K; Wright, Matthew A; Zweifel, Larry; Paninski, Liam; Hen, René; et al. (Neuron (Cambridge, Mass.), 2018)
The hippocampus is traditionally thought to transmit contextual information to limbic structures where it acquires valence. Using freely moving calcium imaging and optogenetics, we show that while the dorsal CA1 subregion of the hippocampus is enriched in place cells, ventral CA1 (vCA1) is enriched in anxiety cells that are activated by anxiogenic environments and required for avoidance behavior. Imaging cells defined by their projection target revealed that anxiety cells were enriched in the vCA1 population projecting to the lateral hypothalamic area (LHA) but not to the basal amygdala (BA). Consistent with this selectivity, optogenetic activation of vCA1 terminals in LHA but not BA increased anxiety and avoidance, while activation of terminals in BA but not LHA impaired contextual fear memory. Thus, the hippocampus encodes not only neutral but also valence-related contextual information, and the vCA1-LHA pathway is a direct route by which the hippocampus can rapidly influence innate anxiety behavior.